2006
DOI: 10.1158/1078-0432.ccr-05-2187
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3′-Kinase/AKT Signaling Is Activated in Medulloblastoma Cell Proliferation and Is Associated with Reduced Expression of PTEN

Abstract: Purpose: Medulloblastomas represent the most frequent malignant brain tumors of childhood.They are supposed to originate from cerebellar neural precursor cells. Recently, it has been shown that Sonic Hedgehog^induced formation of medulloblastoma in an animal model is significantly enhanced by activation of the phosphatidylinositol 3 ¶-kinase (PI3K) signaling pathway. Experimental Design: To examine a role for PI3K/AKT signaling in the molecular pathogenesis of human medulloblastoma, we did an immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
135
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 37 publications
11
135
1
Order By: Relevance
“…Indeed, it is possible that AKT1, AKT3 or both isoforms may play crucial roles in brain tumorigenesis given their shared contribution to embryonic development of the CNS . Although elevation of AKT activity is seen more frequently than PTEN mutation in gliomas and medulloblastomas (Schlegel et al, 2002;Hartmann et al, 2006), mutations causing increased activity of any AKT isoform have not been observed frequently. AKT1 amplification has been reported in various human cancers, including a single case of gliosarcoma (Knobbe and Reifenberger, 2003) and AKT3 mutation has been reported in a single case of glioma (Hunter et al, 2006); however, the consequence of this missense mutation (G171R) on the activity of the enzyme is unknown.…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is possible that AKT1, AKT3 or both isoforms may play crucial roles in brain tumorigenesis given their shared contribution to embryonic development of the CNS . Although elevation of AKT activity is seen more frequently than PTEN mutation in gliomas and medulloblastomas (Schlegel et al, 2002;Hartmann et al, 2006), mutations causing increased activity of any AKT isoform have not been observed frequently. AKT1 amplification has been reported in various human cancers, including a single case of gliosarcoma (Knobbe and Reifenberger, 2003) and AKT3 mutation has been reported in a single case of glioma (Hunter et al, 2006); however, the consequence of this missense mutation (G171R) on the activity of the enzyme is unknown.…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 99%
“…Large scale analysis of genomic gains and loss from over 200 medulloblastoma cases found that loss of 10q is a frequent event (Rickert and Paulus, 2004). Despite this, only rare cases of PTEN mutation have been identified in these tumors (Rasheed et al, 1997), instead observing lower levels of PTEN mRNA expression, potentially caused by epigenetic modifications (Hartmann et al, 2006). An important role of PI3K pathway activation in medulloblastoma was recently suggested for tumors driven by mutations in the Shh pathway.…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 99%
“…The following primers were used: fw 5 0 -ccaagcttgacaatggtctccaggatg-3 0 , rev 5 0 -gggaattccctctggatccttatcctcatc-3 0 . The SGNE1-pcDNA4.1Myc/his expression vector was transfected into D283Med cells by nucleofection as described (Hartmann et al, 2006). After 12 h, transfected cells were selected with 400 mg/ml zeocin (Invitrogen).…”
Section: Reintroduction Of Sgne1 Inhibits Medulloblastoma Proliferatimentioning
confidence: 99%
“…Six hours before completion of the experiment, cells were pulse-treated with 3 H-thymidine (3 mCi/ml, Amersham, Munich, Germany). 3 H-thymidine uptake was determined as previously described (Hartmann et al, 2006) and normalized to the basal uptake in the control cells transfected with empty vector. (c) Representative image of a colony formation assay.…”
Section: Reintroduction Of Sgne1 Inhibits Medulloblastoma Proliferatimentioning
confidence: 99%
“…During the last years it has become increasingly clear that activation of PI3K/Akt signalling is an essential anti-apoptotic event and PI3K/Akt directly targets a number of pro-and anti-apoptotic proteins (reviewed in [109]). A majority of both medulloblastoma and neuroblastoma primary tumours constitutively express activated Akt [22,23,110], and inhibition of PI3K/Akt signalling induces apoptosis of neuroblastoma cells [22,25]. Moreover, activated Akt significantly augments Hedgehog-induced medulloblastoma in mice and activation of PI3K/Akt signalling is important for the proliferation of cancer stem cells residing in the perivascular niche following radiation of medulloblastoma [111].…”
Section: Signal Transduction and Apoptosis In Medulloblastoma And Neumentioning
confidence: 99%